Pengaruh Kecerdasan Emosional dan Pemberdayaan Karyawan Terhadap Komitmen Organisasional Melalui Kepuasan Kerja di Dinas Sosial Daerah Istimewa Yogyakarta - Nur Arifan; Fereshti Nurdiana Dihan (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2018)
The research was purposed to find out whether there was any significant of emotional intelligence and employee empowerment to organizational commitment through job satisfaction on Social Service in Special Region of Yogyakarta. The participants of this research are the employees of Social Service in Special Region of Yogyakarta. Quantitative approach was used during data collection which 107 employees had been participated. This study was using SmartPLS 3.0 version to test the hypothesis.The results of this study found that there are significant positive effect of emotional intelligence on organizational commitment, significant positive effect of employee’s empowerment on organizational commitment, significant positive effect of emotional intelligence on job satisfaction, and significant positive effect of organizational commitment on job satisfaction, also there is significant positive effect of job satisfaction on organizational commitment. In addition, this study found the direct influence of emotional intelligence on organizational commitment is greater than indirect influence of emotional intelligence on organizational commitment through job satisfaction, and the direct influence of employee empowerment on organizational commitment is greater than indirect influence of employee empowerment on organizational commitment through job satisfaction.